(untitled) (International Journal of Occupational Safety and Health, 2024)
Introduction: Medical students have to deal with biohazards in laboratories during undergraduate studies and intensive practice in hospitals. Unsafe operators can result in an outbreak of biohazardous pathogens to healthcare workers, the community, and the environment. However, the most common risk factors for laboratory accidents are a lack of perception and knowledge of biosafety and laboratory safety management. This study aimed to assess knowledge and factors influencing the biosafety practices of medical students at Hanoi Public Health University, Vietnam Methods: A cross-sectional study was conducted to assess the biosafety knowledge of all 286 students majoring in a medical laboratory at HUPH from December 2021 to February 2022. Ethical clearance was obtained from the Ethics Committee of Hanoi University of Public Health. The questionnaire has been created based on WHO biosafety guidelines with some modifications according to the local context. The data were collected by face-to-face interviews Results:: Out of the 286 students invited to complete a biosafety questionnaire, 68.6% of students recognized the fundamental principles of biosafety. Additionally, 76.2% and 91% of students correctly identified risk factors and danger signs in the laboratory, respectively. Furthermore, 79.8% of students provided accurate answers to biosafety laboratory troubleshooting questions. Notably, academic performance, students’ year of study, and average scores in biosafety courses had significantly related to the biosafety knowledge. Gender factors and academic performance were related to the rate of obtaining precise knowledge about incident handling and preventing risk factors in the laboratory. Conclusion: The passed rate of biosafety knowledge among medical laboratory students at the University of Public Health was 68.6%. Factors such as the student’s school year, academic performance, average score in the biosafety course number of internships in hospitals significantly affected their biosafety and troubleshooting knowledge in the laboratory.